Shaping and Reshaping the Professional Self - Kašelionytė, Jurgita (Verbum, 2010)
The article introduces the concept of teacher identity and the variety of factors that influence its construction. Teacher identity covers the characteristics which the society assigns to the teacher profession and those which individual teachers attribute to it. Continuous changes in the education system impel teachers to develop specific competences and reshape their role in the teaching process. A survey carried out in Lithuania among English teachers aims to reveal which competences and roles are internalized without a considerable strain, and which cause more problems and discussions, and why. Although the majority of teachers have a positive attitude towards the repositioning of the professional self, respondents of the survey are quite critical about their minimal involvement in the decision making related to education policy. The survey also tries to define the main reasons for teachers’ stress at work, the topic which has been under a close investigation in the recent years. The issues analyzed in this article are illustrated by a review of professional literature devoted to this topic and the findings of a survey. The results prove that the problems discussed in professional literature are of great relevance to the present situation in Lithuanian educational institutions.